PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN REALISTICS MATHEMATICS EDUCATION (RME) PADA MATERI BANGUN DATAR SEGITIGA UNTUK KELAS VII SMP/MTs - Sari, Violita; ', Jalinus; Saragi, Sehatta (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The motivated of this study is the restrict of mathematics learning instruments as supporting learning in Curriculum 2013 . This study aimed to develop mathematics learning instruments with approach Realistic Mathematics Education (RME) on plane of triangle for 7th grade SMP/MTs. Learning instruments in this study are lesson plan and student activity sheet. This study method used is 4D model by Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel that consist of define, design, development, and disseminate, but the study only done to development step. Based on the results, data analysis can be concluded that the study of mathematics is very valid to the average ratings for the lesson plan is 3.68 and the average ratings for the student activity sheet is 3.65. The student worksheet has also reached the practical qualification in mean percentage of student responses 98% in the small group trial.Keywords: Mathematics Learning Instrument, Approach Realistic Mathematics Education (RME), Research and Development.